Victim blaming and character assassination: Media framing of controversial issues of Bangladesh - Nahar, Meherun; Tabassum, Tasnim; Nisa, Rafikatun (Universitas Negeri Yogyakarta, 2023)
News framing plays a significant role in creating and diverting perceptions on controversial issues in Bangladesh. The study examines three selected occurrences involving renowned personalities to discover the factors that contribute to the sensationalization of news information. The research posits theme-based criteria that influence news framing and investigates how controversy spreads via conventional and internet media. According to the study, online news portals participate in more news framing than conventional media. Victim blaming and character assassination are frequent framing strategies utilized in the online domain. The framing factors include misleading headlines, improper wording, and distortion of context. Thematic analysis of the study finds nine variables responsible for framing disagreement in the media, three of which constitute a basic pattern for framing disputes. The study emphasizes the possibility of news framing interfering with an individual's personal and professional life, as well as the importance of responsible journalism that promotes factual reporting while avoiding framing elements that can lead to victim blaming, character assassination, and sensationalism. Overall, the study adds to the current literature on news framing by offering insights into the thematic factors that can greatly influence framing debate. The study's findings might be useful for media practitioners and policymakers in Bangladesh and abroad since they give a better knowledge of the mechanics of framing disputes in the media. The report also recommends more research on news framing and its influence on public perceptions and attitudes toward contentious subjects.